Clinical academic careers for general practice nurses: a rapid evidence assessment. (August 2021) - Bradbury, Andrew; Shortland, Sue; Jones, Sarahjane; Hewett, Fraser; Karen Storey,
Background: Clinical academics are health professionals who provide direct patient care alongside engaging in health research. Despite the generally agreed consensus that such roles enhance evidence-based care, availability and uptake has been sporadic in non-medical professions. With no data readily available regarding general practice nurses undertaking clinical academic roles, there is a need to understand the barriers and enabling factors that impact general practice nurses considering or pursuing a clinical academic career. Aims: This review aims to address the question 'What are the barriers and enablers relevant to general practice nurses in the UK pursuing clinical academic careers?' by providing an overview of the relevant existing literature and drawing out the implications for policy and practice. Methods: Literature published in the past 10 years was systematically searched. Using agreed inclusion criteria, papers were first screened on titles and abstracts, with papers included at this stage reviewed as full texts. Results: Thirteen papers met the criteria for inclusion. The extraction and synthesis of findings allowed for the development of three themes: roles and responsibilities; embarking on a clinical academic career; and organisational research culture. Conclusions: Findings suggest that infrastructure developments are required across higher education institutions and general practice organisations to bring about a cultural change to equip and empower general practice nurses to consider and pursue clinical academic careers.